Treatment of Intradural Spinal Arteriovenous Fistula: Technical Case Report - Palmiero, Helbert de Oliveira Manduca; Caramanti, Ricardo Lourenço; Chaddad-Neto, Feres Eduardo Aparecido (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Although rare, arteriovenous fistula (AVF) is the most common vascular malformation of the spine, and it is mainly located in the thoracic region. The fistula is identified by arteriography, which enables the treatment by embolization or guides the microsurgical therapy.Clinical Presentation We describe the case of a 61-year-old woman with neurogenic claudication evolving to paraparesis. A dorsal intradural AVF was identified by magnetic resonance imaging (MRI) and arteriography, and it was submitted to an embolization, but the procedure was unsuccessful. The patient was then referred for neurosurgery, and the AVF was obliterated using a microsurgical technique guided by multimodal intraoperative monitoring. We identified the AVF in the intraoperative moment and we then cut and coagulated the extradural portion of the nerve root.Discussion Arteriovenous fistulas occur in the dura mater of the nerve roots with the arterialization of the venous plexus. The treatment prevents the progression of the deficits. While performing diagnostic arteriography, attempts of embolization are possible.Conclusion Although the initial attempt of embolization at the moment of the diagnostic arteriography is achievable, it has failure rates of 50%, unlike the surgical treatment, which is definitive in all cases, as reported in this article.
Keywords: intradural spinal arteriovenous fistula; embolization; microsurgical technique